Functional Study of Cytochrome P450 Enzymes from the Brown Planthopper (Nilaparvata lugens Stål) to Analyze Its Adaptation to BPH-Resistant Rice - Peng, Lei; Zhao, Yan; Wang, Huiying; Song, Chengpan; Shangguan, Xinxin; Ma, Yinhua; Zhu, Lili; He, Guangcun (Frontiers in Physiology, 2017)
Plant-herbivore interactions form a complex system. Plants synthesize toxic compounds as the main defense strategy to combat herbivore assault, whereas insects deploy detoxification systems to address toxic plant compounds. The P450s are some of the main detoxification enzymes employed by insects to combat chemical defenses in host plants. In this study, we used rice and its piercing-sucking insect pest specialist the brown planthopper (BPH) [Nilaparvata lugens Stål (Hemiptera: Delphacidae)] to constitute an ideal system for studying plant-insect interactions. By feeding the BPHs artificial diets containing ethanol extracts, we showed that biotype Y BPHs had a greater ability to metabolize exogenous substrates than biotype 1 BPHs. NlCPR knockdown inhibited the ability of BPHs to feed on YHY15. qRT-PCR was used to screen the genes in the P450 family, and the upregulation of CYP4C61, CYP6AX1 and CYP6AY1 induced by YHY15 was investigated. When the three P450 genes were knocked down, only CYP4C61 dsRNA treatment inhibited the ability of BPHs to feed on YHY15. These results indicated that the BPH P450 enzymes were a key factor in physiological functions of BPH when feeding on BPH-resistant rice. In summary, our results reveal the interaction between the mediated defense of the allelochemicals of BPH-resistant rice genes and the BPH detoxiﬁcation system consisting of the P450s.